Cardiovascular autonomic neuropathy and the impact on progression of diabetic kidney disease in type 1 diabetes. Issue 1 (13th October 2021) - Bjerre-Christensen, Theis; Winther, Signe A; Tofte, Nete; Theilade, Simone; Ahluwalia, Tarunveer S; Lajer, Maria; Hansen, Tine W; Rossing, Peter; Hansen, Christian Stevns
Abstract : Introduction: We investigated the association between cardiovascular autonomic neuropathy (CAN) and decline in kidney function in type 1 diabetes. Research design and methods: We included 329 persons with type 1 diabetes. CAN was assessed by cardiovascular reflex tests (CARTs): heart rate response to deep breathing (E/I ratio), to standing (30/15 ratio) and to the Valsalva maneuvre. Two or more pathological CARTs defined CAN diagnosis. Outcomes were yearly change in albuminuria or yearly change in estimated glomerular filtration rate (eGFR). An endpoint of eGFR decline >30%, development of end-stage kidney disease (ESKD) or death was examined. Associations were assessed by linear and Cox regression. Results: Participants were aged 55.2 (9.4) years, 52% were male, with a diabetes duration of 40.1 (8.9) years, HbA1c of 7.9% (62.5 mmol/mol), eGFR 77.9 (27.7) mL/min/1.73 m 2, urinary albumin excretion rate of 14.5 (7–58) mg/24 hours, and 31% were diagnosed with CAN. CAN was associated with a 7.8% higher albuminuria increase per year (95% CI: 0.50% to 15.63%, p=0.036) versus no CAN. The endpoint of ESKD, all-cause mortality and ≥30% decline in eGFR was associated with CAN (HR=2.497, p=0.0254). Conclusion: CAN and sympathetic dysfunction were associated with increase in albuminuria in individuals with type 1 diabetes suggesting its role as a potential marker of diabetic kidney disease progression.